Bioenergy knowledge, perception and attitude among students at Jambi state senior high school. Issue 1 (February 2021) - Nazarudin,; Hasibuan, M P H; Haryadi, B; Nurhayati,; Ulyarti,; Hadiyanto,
Abstract: Bioenergy is one of the renewable energies which is predicted to be a main energy in the next few years. It can play the important role to change the current fossil fuel-based energy into a green energy which has a low carbon footprint. A research about how to develop a bioenergy have been done by a lot of reseacher. However, especially in Indonesia, there is just few research to study about bioenergy from societal aspects poin of view such as the understanding and awarness of bioenergy among citizens. In this research, we have investigated senior high school students' knowledge, perceptions, and attitudes interconected to bioenergy with online survery. The survey instrument used in the study was adopted from P. Halder's study. The data was collected from students at senior high school th (SMAN 10) Jambi City. The results showed that the students awareness of bioenergy perceived from school, home, and social media have significant effects on their knowledge, perceptions and attitudes related to bioenergy. Among 211 students as respondent (N), we found 70.62% believe that they understand well the concept about bioenergy, 5.21% believe that they understand it very well, and the rest believe that they do not understand it. This understanding reflects to their willingness to use a bioenergy in their daily life, in which 71.70% respondents agree to use bioenergy, 25.47% respondents can not decide, and only 2.83% do not want to use it. To find the relationship among the variables, a multiple regression was conducted. A statistical analysis showed that the model for knowledge as a function of attitudes and perception does not fit the data therefore this model is rejected. However, both model for attitudes as function of perception and knowledge, and also perception as function of attitudes and knowldeges fit the data hence the models are accepted. In other words, attitudes of students who will use/not use bioenergy, is significantly affected by their perception about bioenergy.